Mechanism of Bone Metabolism Interruption Due to High Intensity Physical Exercise - Gadis Meinar Sari, - (0975-8453, 2020)
Background: High-intensity physical exercise affects the increase of cortisol secretion which knows as the main glucocorticoid in the body and causes a decrease in osteoprotegerin (OPG) activity. Glucocorticoids also work directly on osteoblasts and osteocytes through glucocorticoid receptors (GRÎ±). Aims: this study aimed to prove the mechanism of bone metabolism disorders due to high-intensity physical exercise through changes in glucocorticoid levels, osteoprotegerin, osteocalcin, c-telopeptide and the number of apoptotic osteoblasts. Method: an experimental study with a quasy-experimental design was used. Object used was 20 female white rats of approximately 3 months of age divided into the control and treatment groups. In the treatment group was given swimming training with 18% weight gain within 90% of the maximum time, carried out 2 times per set with a frequency of 3 times per week within 8 weeks. The data obtained were analyzed by t-test 2 independent samples and path analysis. Result: The results of analysis showed an effect of high-intensity physical exercise on glucocorticoid levels (É¤=0.79); glucocorticoid levels affected the level of osteoprotegerin (É¤=-0.688) and osteocalcin (Î²=-0.48), however it did not affect the number of apoptotic osteoblasts (É¤=0.21); osteoprotegerin levels affected c-telopeptide levels (Î²=-0.65); the number of apoptotic osteoblasts had no affected on osteocalcin levels (Î²=-0.19); levels of c-telopeptide (Î²=0.82) and osteocalcin (Î²=-0.22) affect the c-telopeptide or osteocalcin ratio. Conclusion: The mechanism of bone metabolism on high-intensity physical exercise is caused by the increase of glucocorticoid levels which makes a decrease in osteoprotegerin levels and affects on the rise of c-telopeptide levels.